Islamic Law Analysis About Eligibility Honorary Teacher Salaries in Perspective School of thought Syafi'i (Case Study of Dharma Bakti Education Foundation, Subdistrict Finished Regency Langkat) - Cindy Fadila; Khairul Mufti Rambe (Fox Justi : Jurnal Ilmu Hukum, 2025)
Salary, wages are a form of appreciation given by employers to workers for the work that has been done. In increasing the participation of Tasu Teacher Professionalism as a worker, nowadays they also participate in family welfare, one of which is becoming a teacher. Provisions on wages and forms of protection of special rights are given to workers. This study aims to answer the questions that are the formulation of the problem, namely to find out about the Analysis of Islamic Law on the Eligibility of Honorary Teacher Salaries in the Perspective of the Syafi'I School of Law Case study of the Dharma Bakti Foundation, Selamat District, Langkat Regency. This study uses qualitative research, data collected by interviews, observation, then with descriptive analysis methods. The results of the study that researchers can get by adjusting and the views of the Syafi'i School of Law, the provision of salaries or wages at the Dharma Bakti Foundation is not appropriate because there is no certainty of the salary of the Honorary Teacher.